1983
DOI: 10.1139/v83-412
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-induced chemical shifts in 3- and 4-substituted styrenes: definition of substituent constants and determination of mechanisms of transmission of substituent effects by iterative multiple linear regression

Abstract: Iterative multiple linear regression analysis of substituent-induced chemical shifts in 3- and 4-substituted styrene derivatives is used to redefine σF and [Formula: see text] substituent constants (with respective standard errors of ca. 0.01 and 0.005). Correlations with the data for various model systems indicate that these substituent constants are applicable to data sets involving both chemical shift and acidity measurements in aprotic media. The approach we have used involving a homogeneous data set with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…The question of whether predicted a, (3, and Q are pure 0 factors or rather linear combinations of a,, a,, and the actual factors is probably best addressed by correlation analysis. This is reported in the subsequent paper (29).…”
Section: (0 Factor Analysis Incorporating Short-rcznge Chemical Shiftssupporting
confidence: 58%
See 2 more Smart Citations
“…The question of whether predicted a, (3, and Q are pure 0 factors or rather linear combinations of a,, a,, and the actual factors is probably best addressed by correlation analysis. This is reported in the subsequent paper (29).…”
Section: (0 Factor Analysis Incorporating Short-rcznge Chemical Shiftssupporting
confidence: 58%
“…The first two are totally independent of a, and (T:. This allows us to separate electronic ((T, and (T:) contributions from other short-range, non-electronic contributions (29 chemical shifts in a large number of haloaromatic and haloalkene derivatives. They concluded that two major and one minor factor were necessary to account for the chemical shifts, compared to four major and one minor factor according to this investigation.…”
Section: (0 Factor Analysis Incorporating Short-rcznge Chemical Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the value for the nitro group was confirmed as 0.15. 156 based a similar operation on 13 C substituent chemical shifts of meta-and para-substituted styrenes. Iterative multiple regression was used for the redefinition of the I and 0 R scales.…”
Section: A Experimental Techniquesmentioning
confidence: 99%
“…The I3C chemical shifts of many styrene derivatives, as well as the 'H shifts of their olefinic protons, have been extensively studied and interpreted (29)(30)(31)(32)(33), notably by Reynolds and coworkers. Here we note that H-4 in styrene is shielded by 0.10 ppm relative to benzene at the same concentration (footnote in Table 1).…”
Section: Proton Chemical Shiftsmentioning
confidence: 99%